2023
DOI: 10.1093/nar/gkac1247
|View full text |Cite
|
Sign up to set email alerts
|

Annotation of uORFs in the OMIM genes allows to reveal pathogenic variants in 5′UTRs

Abstract: An increasing number of studies emphasize the role of non-coding variants in the development of hereditary diseases. However, the interpretation of such variants in clinical genetic testing still remains a critical challenge due to poor knowledge of their pathogenicity mechanisms. It was previously shown that variants in 5′-untranslated regions (5′UTRs) can lead to hereditary diseases due to disruption of upstream open reading frames (uORFs). Here, we performed a manual annotation of upstream translation initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…To aid the assessment of 5’UTR variant pathogenicity, in silico tools have recently been developed, with an emphasis put on uORF-perturbing variants [ 20 , 26 ]. A systematic characterization of this class of 5’UTR variants showed that they are subject to strong negative selection, which could even be equivalent to that observed against missense variants [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To aid the assessment of 5’UTR variant pathogenicity, in silico tools have recently been developed, with an emphasis put on uORF-perturbing variants [ 20 , 26 ]. A systematic characterization of this class of 5’UTR variants showed that they are subject to strong negative selection, which could even be equivalent to that observed against missense variants [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, functional evidence is necessary to support their pathogenicity and hence confirm the molecular diagnosis. Recently, to close the annotation and interpretation gap, several in silico tools [ 20 26 ] and guidelines [ 27 ] have been developed, although their specific applicability to the accurate and comprehensive interpretation of the diverse pathogenic mechanism of 5’UTR variants is yet to be fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, functional evidence is necessary to support their pathogenicity and hence confirm the molecular diagnosis. Recently, to close the annotation and interpretation gap, several in silico tools [20][21][22][23][24][25][26] and guidelines 27 have been developed, although their specific applicability to the accurate and comprehensive interpretation of the diverse pathogenic mechanism of 5'UTR variants is yet to be fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Although long-read sequencing technology improves the identification of structural variations, the analytical challenge around variant interpretation persists, especially for balanced structural variations with noncoding breakpoints [6][7][8] . Noncoding regions, representing approximately 98% of the human genome, have recently attracted attention in relation to genetically unsolved patients with Mendelian disorders [9][10][11] . To date, a number of noncoding variants have been identified, most of which were recognized according to a physical location in or adjacent to the known disease-causing gene, such as intronic, regulatory, upstream or downstream regions of known genes.…”
mentioning
confidence: 99%